Photoelectrochemical Degradation of Dye Pollutants Using Tio2 Thin Film Electrodes - Lee, Chong Yong (2004)
Thin film electrodes were fabricated by immobilizing titanium dioxide (Ti02) onto titanium substrate using sol gel dip-coating method. The electrochemical technique was employed to study the photodegradation process on methyl orange dye. The effects of various parameters and conditions on electrochemical assisted photocatalytic degradation process were investigated by monitoring dyes decolourisation rates using UV-Vis spectrophotometer. Photosensitivity of the Ti02 thin film electrode was analysed by Linear Sweep Voltammetry (LSV) and Cyclic Voltamrnetry (CV) techniques combined with illumination. Sample heat-treated at 500°C showed the best photosensitivity. The TiOz thin films and the dried gel were also analysed using Scanning Electron Microscope (SEM), X-Ray Diffiactometry (XRD), UV/Vis Spectroscopy, Fourier Transform-Infra Red (FT-IR), Thennogravimetric Analyser (TGA), Differential Thermal Analyser (DTA) and CHNS analyser. The photoelectrochemical degradation experiment results showed that the rate of dye removal increased with external applied potential between 0.0 V and 1.5 V versus AgIAgCl reference electrode. Meanwhile, the photoeletrochemical degradation rate was also affected by initial concentrations, light intensity, light sources, photocatalysts coated area, repeated use, supporting electrolyte, solution pH, agitation and solution temperature. The photoelectrochemical degradation experiment was also camed out on naphtol blue black, rhodamine 6G, methylene blue, reactive blue 2, direct red 81, mixed dyes (consists of methyl orange, naphtol blue black, rhodamine 6G, methylene blue, reactive blue 2, direct red 8 1) and actual textile effluents. The removal efficiency was evaluated and compared in terms of UV/Vis decolourisation, Total Organic Carbon (TOC), Chemical Oxygen Demand (COD) and Biological Oxygen Demand (BOD).